Flavoprotein fluorescence elevation is a marker of mitochondrial oxidative stress in patients with retinal disease - Ahsanuddin, Sofia; Rios, Hernan A.; Otero-Marquez, Oscar; Macanian, Jason; Zhou, Davis; Rich, Collin; Rosen, Richard B. (Frontiers in Ophthalmology, 2023)
Purpose Recent studies of glaucoma, age-related macular degeneration, and diabetic retinopathy have demonstrated that flavoprotein fluorescence (FPF) can be utilized non-invasively as an indicator of mitochondrial oxidative stress in the retina. However, a comprehensive assessment of the validity and reliability of FPF in differentiating between healthy and diseased eyes across multiple disease states is lacking. Here, we evaluate the sensitivity and specificity of FPF in discriminating between healthy and diseased eyes in four leading causes of visual impairment worldwide, one of which has not been previously evaluated using FPF. We also evaluate the association between FPF and visual acuity. Methods A total of 88 eyes [21 eyes of 21 unaffected controls, 20 eyes from 20 retinal vein occlusion (RVO) patients, 20 eyes from 20 diabetic retinopathy (DR) patients, 17 eyes from 17 chronic exudative age-related macular degeneration (exudative AMD) patients, and 10 eyes from 10 central serous retinopathy (CSR) patients] were included in the present cross-sectional observational study. Eyes were imaged non-invasively using a specially configured fundus camera OcuMet Beacon® (OcuSciences, Ann Arbor, MI). The macula was illuminated using a narrow bandwidth blue light (455 – 470 nm) and fluorescence was recorded using a narrow notch filter to match the peak emission of flavoproteins from 520 to 540 nm. AUROC analysis was used to determine the sensitivity of FPF in discriminating between diseased eyes and healthy eyes. Nonparametric Kruskal-Wallis Tests with post-hoc Mann Whitney U tests with the Holm-Bonferroni correction were performed to assess differences in FPF intensity, FPF heterogeneity, and best corrected visual acuity (BCVA) between the five groups. Spearman rank correlation coefficients were calculated to assess the relationship between FPF and BCVA. Results AUROC analysis indicated that FPF intensity is highly sensitive for detecting disease, particularly for exudative AMD subjects (0.989; 95% CI = 0.963 – 1.000, p=3.0 x 107). A significant difference was detected between the FPF intensity, FPF heterogeneity, and BCVA in all four disease states compared to unaffected controls (Kruskal-Wallis Tests, p = 1.06 x 10-8, p = 0.002, p = 5.54 x 10-8, respectively). Compared to healthy controls, FPF intensity values were significantly higher in RVO, DR, exudative AMD, and CSR (p < 0.001, p < 0.001, p < 0.001, and p = 0.001, respectively). Spearman rank correlation coefficient between FPF intensity and BCVA was ρ = 0.595 (p = 9.62 x 10-10). Conclusions Despite variations in structural retinal findings, FPF was found to be highly sensitive for detecting retinal disease. Significant FPF elevation were seen in all four disease states, with the exudative AMD patients exhibiting the highest FPF values compared to DR, CSR, and RVO subjects. This is consistent with the hypothesis that there is elevated oxidative stress in all of these conditions as previously demonstrated by blood studies. FPF intensity is moderately correlated with the late-in disease-marker BCVA, which suggests that the degree of FPF elevation can be used as a metabolic indicator of disease severity.